Sense and antisense RNA products of the uxuR gene can affect motility and chemotaxis acting independent of the UxuR protein - Tutukina, Maria N.; Dakhnovets, Artemiy I.; Kaznadzey, Anna D.; Gelfand, Mikhail S.; Ozoline, Olga N. (Frontiers in Molecular Biosciences, 2023)
Small non-coding and antisense RNAs are widespread in all kingdoms of life, however, the diversity of their functions in bacteria is largely unknown. Here, we study RNAs synthesised from divergent promoters located in the 3’-end of the uxuR gene, encoding transcription factor regulating hexuronate metabolism in Escherichia coli. These overlapping promoters were predicted in silico with rather high scores, effectively bound RNA polymerase in vitro and in vivo and were capable of initiating transcription in sense and antisense directions. The genome-wide correlation between in silico promoter scores and RNA polymerase binding in vitro and in vivo was higher for promoters located on the antisense strands of the genes, however, sense promoters within the uxuR gene were more active. Both regulatory RNAs synthesised from the divergent promoters inhibited expression of genes associated with the E. coli motility and chemotaxis independent of a carbon source on which bacteria had been grown. Direct effects of these RNAs were confirmed for the fliA gene encoding σ28 subunit of RNA polymerase. In addition to intracellular sRNAs, promoters located within the uxuR gene could initiate synthesis of transcripts found in the fraction of RNAs secreted in the extracellular medium. Their profile was also carbon-independent suggesting that intragenic uxuR transcripts have a specific regulatory role not directly related to the function of the protein in which gene they are encoded.